2013
DOI: 10.1259/bjr.20130160
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intrascanner variability of pulmonary nodule volumetry on low-dose 64-row CT: an anthropomorphic phantom study

Abstract: Objective: To assess inter-and intrascanner variability in volumetry of solid pulmonary nodules in an anthropomorphic thoracic phantom using low-dose CT. Methods: Five spherical solid artificial nodules [diameters 3, 5, 8, 10 and 12 mm; CT density 1100 Hounsfield units (HU)] were randomly placed inside an anthropomorphic thoracic phantom in different combinations. The phantom was examined on two 64-row multidetector CT (64-MDCT) systems (CT-A and CT-B) from different vendors with a low-dose protocol. Each CT e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
1
14
0
1
Order By: Relevance
“…In the NELSON study, slice thickness of 1.0 mm with reconstruction interval of 0.7 mm was used to provide isometric voxels for accurate semi-automated volume measurements. These semi-automated measurements were found to be highly reproducible for the large majority of solid nodules, also in phantom studies [27][28][29], with high reader agreement and volume differences >15% between two readers in only 4% of solid nodules [27][28][29]. Besides, in Lindell's study lung cancer growth curves were plotted and visually evaluated, but growth patterns were not quantified.…”
Section: Discussionmentioning
confidence: 91%
“…In the NELSON study, slice thickness of 1.0 mm with reconstruction interval of 0.7 mm was used to provide isometric voxels for accurate semi-automated volume measurements. These semi-automated measurements were found to be highly reproducible for the large majority of solid nodules, also in phantom studies [27][28][29], with high reader agreement and volume differences >15% between two readers in only 4% of solid nodules [27][28][29]. Besides, in Lindell's study lung cancer growth curves were plotted and visually evaluated, but growth patterns were not quantified.…”
Section: Discussionmentioning
confidence: 91%
“…For the screening, 16-detector or, in later rounds 64-detector CT scanners in low-dose setting were used, without the administration of intravenous contrast media. Images were analysed using semiautomated software (LungCARE, version Somaris/5 VA70C-W, Siemens Medical Solutions) 9 15. The analysis included the semiautomated segmentation of nodules and determination of the nodule volume.…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al 17 showed that there was no benefit for double reading consensus with the use of semiautomated software. More detailed descriptions of the equipment and execution of the screening examination have been provided in previous reports 9 15 18…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A larger number of results derived from studies using newer generation scanners did not confirm the previous observations. Indeed, the introduction of iterative reconstructions, employed to increase image quality in favour of a further reduction of the effective radiation dose, demonstrated an even better performance compared to that of the traditionally used filtered-back projection reconstructions [101][102][103][104][105][106][107][108][109][110][111][112].…”
Section: Factors Influencing Nodule Measurement Variationsmentioning
confidence: 99%